Japan's China policy on Yasukuni under Abe (2012–2015): a political survival interpretation. Issue 1 (2nd January 2017) - Cheung, Mong
ABSTRACT: This article examines Japan's different responses toward China's pressure over the Yasukuni issue during the second Abe administration. It is generally taken for granted that Japan's official responses to China's pressure over the issue are determined by the personality of individual leaders and the emergence of Japanese conservative nationalism. With the examination of cases during the second Abe administrations since 2012, this article offers an alternative interpretation by highlighting the rationality of prime minister and the primacy of domestic political survival of individual leader. The article suggests that domestic political legitimacy of individual leaders is a vital factor that affects Japan's China policy on Yasukuni.